2017
DOI: 10.1007/s00520-017-3965-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in symptom management experiences during breast cancer treatment

Abstract: This study elucidates opportunities for future research aimed at improving equity for cancer treatment-related symptom management. For Black women, warnings about anticipated symptoms and treatment for ongoing symptoms were particular areas of concern. Routine symptom assessment for all women, as well as clinicians' management of symptoms for racially diverse cancer patients, need to be more thoroughly studied and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
(47 reference statements)
2
23
0
Order By: Relevance
“…However, we did find that clinician underestimation of certain symptoms was greater in nonwhite patients than white patients. This finding warrants further research but also reflects the larger literature documenting racial disparities in patient‐provider communication 30‐33 as well as racial differences in symptom management experiences 34 …”
Section: Discussionsupporting
confidence: 56%
“…However, we did find that clinician underestimation of certain symptoms was greater in nonwhite patients than white patients. This finding warrants further research but also reflects the larger literature documenting racial disparities in patient‐provider communication 30‐33 as well as racial differences in symptom management experiences 34 …”
Section: Discussionsupporting
confidence: 56%
“…The study designs included 6 randomized controlled trials (RCTs), 18,20,22,26,30,33 1 prospective cohort, 19 12 retrospective cohort, 21,[23][24][25]29,35,[37][38][39][40]43,44 2 case-cohort, 27,40 5 case-control, 17,32,34,36,42 and 3 cross-sectional studies (2 combined with retrospective cohorts) 23,31,32 (Table 1). Most studies were conducted among chronic noncancer pain patients (n = 15) 19-26,30,33,35,39,40,43,44 ; however, some studies were conducted among all opioid users including cancer and acute pain patients ( Table 1).…”
Section: Study Design and Population Characteristicsmentioning
confidence: 99%
“…Moreover, the absence of evidence based on specific clinical subpopulations (eg, women, minorities, acute trauma, and elective surgery) or specific opioid formulations meant that the guidelines adopted a one‐size‐fits‐all approach for the many pain‐inducing conditions, regardless of pain etiology and biologic variation among patient subpopulations. Notably, there is a lack of data on effective noncancer pain management among African‐Americans, which is concerning given mixed evidence on racial differences in pain and prescribing . These critical research gaps need to be addressed if prescribing behavior is to become more evidence‐based.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 11 , 12 , 13 , 14 Several studies compared symptoms during or after chemotherapy by race/ethnicity and found mixed results. 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Symptom assessment timing varied in these studies (eg, during treatment vs later in survivorship), which may explain the inconsistent findings. To our knowledge, no studies have compared differences in patient-reported symptoms before starting chemotherapy.…”
Section: Introductionmentioning
confidence: 93%